Viva on Pre-clinical Endodontics and Conservative Dentistry - (For 2nd Year BDS Students) - Kothari Kamna; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2010)
Contains 14 chapters, beginning with a chapter on Introduction, Definition, Aim and Scope of Conservative Dentistry, followed by classification, nomenclature, Various Chair Side Positions, Tooth Numbering Systems, Restorations, Operative Instruments, Rotary Cutting Instruments, Finishing and Polishing of Restorations with last chapter on Root Canal Instruments.
Keywords: Conservative Dentistry and Endodontics,MCQs and Self-assessment; Electronic books